Controlled Turning Process for the Production of Friction-Reduced Cylinder Liners with a Defined Free-Form Geometry - Berend Denkena; Benjamin Bergmann; Miriam Handrup; Christopher Schmidt (Journal of Machine Engineering)
Friction in the piston-cylinder system of combustion engines has a great influence on fuel consumption. To reduce the friction of combustion engines, free-form cylinder liners and microstructured cylinder liners have proven to be advantageous. However, the combination of both processes is not industrially realized today because of an increased manufacturing effort due to a higher number of process steps. To save re-sources in form of honing oil in the production, the free-form can be machined by a dry turning process instead of form honing. A combination with the microstructuring process in a single manufacturing step would furthermore reduce non-productive time. This paper presents a piezo-actuated hybrid tool that can carry out both processes. The tool wear and the behavior during free-form fine machining of cylinder lin-ers are investigated. A process control system is introduced that controls the cylinder liner geometry by adapting the process parameters during free-form turning.